2007
DOI: 10.1016/j.neuron.2007.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Two Gr Genes Underlie Sugar Reception in Drosophila

Abstract: We have analyzed the molecular basis of sugar reception in Drosophila. We define the response spectrum, concentration dependence, and temporal dynamics of sugar-sensing neurons. Using in situ hybridization and reporter gene expression, we identify members of the Gr5a-related taste receptor subfamily that are coexpressed in sugar neurons. Neurons expressing reporters of different Gr5a-related genes send overlapping but distinct projections to the brain and thoracic ganglia. Genetic analysis of receptor genes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
517
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 404 publications
(565 citation statements)
references
References 41 publications
27
517
4
Order By: Relevance
“…The orthologous genes of these threeCO2 receptors were also identified in other mosquito species such as Aedes aegypti (Erdelyan et al 2012) and Culex quinquefasciatus (Robertson and Kent 2009). Recently published genome and transcriptome sequences from various insect species revealed that putative CO2 gustatory receptors are conserved in many insect species including mosquitoes, moths, butterflies, beetles and flies (Anderson et al 2009;Briscoe et al 2013;Dahanukar et al 2007;Erdelyan et al 2012;Obiero et al 2014). However, CO2 GRs are absent in other species like honeybees, human louses, wasps, ants and blacklegged ticks (Robertson and Kent 2009), suggesting that these latter species may use different mechanisms for CO2 sensation.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…The orthologous genes of these threeCO2 receptors were also identified in other mosquito species such as Aedes aegypti (Erdelyan et al 2012) and Culex quinquefasciatus (Robertson and Kent 2009). Recently published genome and transcriptome sequences from various insect species revealed that putative CO2 gustatory receptors are conserved in many insect species including mosquitoes, moths, butterflies, beetles and flies (Anderson et al 2009;Briscoe et al 2013;Dahanukar et al 2007;Erdelyan et al 2012;Obiero et al 2014). However, CO2 GRs are absent in other species like honeybees, human louses, wasps, ants and blacklegged ticks (Robertson and Kent 2009), suggesting that these latter species may use different mechanisms for CO2 sensation.…”
Section: Introductionmentioning
confidence: 98%
“…Two gustatory receptors (GRs), DmelGR21a and DmelGR63a, were identified through their expression in ab1C olfactory receptor neurons in the CO2-sensitive ab1 sensilla on the antennae (Dahanukar et al 2007;Jones et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations